The role of calcium-independent phospholipase A(2)γ in modulation of aqueous humor drainage and Ca(2+) sensitization of trabecular meshwork contraction - Pattabiraman, Padmanabhan P. (American Physiological Society, 2012)
The contractile and relaxation characteristics of trabecular meshwork (TM) are presumed to influence aqueous humor (AH) drainage and intraocular pressure. The mechanisms underlying regulation of TM cell contractile properties, however, are not well understood. This study investigates the role of calcium-independent phospholipase A(2) (iPLA(2)), which controls eicosanoid synthesis, in regulation of TM cell contraction and AH outflow using mechanism-based isoform specific inhibitors (R)-bromoenol lactone (R-BEL, iPLA(2)γ specific) and (S)-bromoenol lactone (S-BEL, iPLA(2)β specific). Immunohistochemical analysis revealed intense staining for both iPLA(2)β and γ isoforms throughout the TM, juxtacanalicular tissue, and Schlemm's canal of human eye. Inhibition of iPLA(2)γ by R-BEL or small interfering RNA-mediated silencing of iPLA(2)γ expression induced dramatic changes in TM cell morphology, and decreased actin stress fibers, focal adhesions, and myosin light-chain (MLC) phosphorylation. AH outflow facility increased progressively and significantly in enucleated porcine eyes perfused with R-BEL. This response was associated with a significant decrease in TM tissue MLC phosphorylation and alterations in the morphology of aqueous plexi in R-BEL-perfused eyes. In contrast, S-BEL did not affect either of these parameters. Additionally, R-BEL-induced cellular relaxation of the TM was associated with a significant decrease in the levels of active Rho GTPase, phospho-MLC phosphatase, phospho-CPI-17, and arachidonic acid. Taken together, these observations demonstrate that iPLA(2)γ plays a significant and isoform-specific role in regulation of AH outflow facility by altering the contractile characteristics of the TM. The effects of iPLA(2)γ on TM contractile status appear to involve arachidonic acid and Rho GTPase signaling pathways.